Hepatitis B virus: new therapeutic perspectives. (January 2016) - Lin, Chih‐Lin; Yang, Hung‐Chih; Kao, Jia‐Horng
Abstract: Current antiviral therapies have dramatically improved the long‐term outcomes of patients with chronic hepatitis B virus (HBV) infection. Both interferon (IFN) and nucleos(t)ide analogue (NA) treatments have been shown to reduce the progression of liver disease in chronic hepatitis B (CHB) patients. However, persistent covalently closed circular DNA (cccDNA) can result in a viral relapse after discontinuation of antiviral treatment. On the basis of extensive research on the HBV lifecycle and virus–host interactions, several new agents focusing on viral and host targets are under development to cure HBV. New polymerase inhibitors, tenofovir alafenamide and besifovir provide effective and safer treatment for CHB patients. Agents targeting cccDNA, such as engineered site‐specific nucleases and RNA interference therapeutics could eliminate cccDNA or silence cccDNA transcription. Inhibitors of HBV nucleocapsid assembly suppress capsid formation and prevent synthesis of HBV DNA. The HBV entry inhibitor, Myrcludex‐B, has been shown to effectively inhibit amplification of cccDNA as well as the spread of intrahepatic infection. Agents targeting host factors that enhance innate and adaptive immune responses, including the lymphotoxin‐β receptor agonist, toll‐like receptor agonist, immune checkpoint inhibitors and adenovirus‐based therapeutic vaccine, could play a critical role in the elimination of HBV‐infected cells. With all of these promising approaches, we hope to reach the ultimate goal of a cure to HBV in the near future.